Examining predictors of help-seeking behaviours in patients with mood and anxiety symptoms. (July 2018) - Fine, A; Nasiri, K; Fotinos, K; Anand, L; Furtado, M; Armata, RS; Badali, K; Mincer, J; Mincer, M; Epstein, I; Cameron, C; Guthrie, A; et al.
Highlights: Help-seeking behaviours are predicted by anxiety sensitivity and marital status. The ability to discuss mood and anxiety symptoms with doctors predicts likelihood of additionally seeking treatment. Increased comorbidity of mental health disorders increases help-seeking behaviours. Disorder type and demographic variables have a complex relationship when predicting help-seeking behaviour. Abstract: Relatively little is known about individual characteristics that factor into the decision to seek help for mood and anxiety symptoms. The current study was undertaken in order to examine factors that predict the likelihood of seeking help for mood and anxiety symptoms amongst a clinical population. Patients ( N = 278) referred to a tertiary care clinic in Toronto, Canada were asked about their help-seeking behaviours (HSB) through initial intake assessments and self-administered questionnaires, including the Beck Anxiety Inventory, Anxiety Sensitivity Index, Intolerance of Uncertainty Scale, and Beck Depression Inventory-II. Correlates of anxiety and depression were examined to determine whether they could predict HSB amongst individuals with Generalized Anxiety Disorder with or without comorbid Major Depressive Disorder, as well as Panic Disorder and Social Anxiety Disorder. Psychiatric diagnoses were then examined to determine whether comorbidity and demographic factors impacted HSB. Results indicated that there were significant differences in anxiety and depression correlating mainly with anxiety sensitivity, as a predictor of HSB, and that there is a complex relationship between disorder type and demographic variables. The implications of these findings and suggested targeted interventions are discussed.